2021
DOI: 10.3389/fcell.2021.645501
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing in a Cohort of High Myopia Patients in Northwest China

Abstract: High myopia (HM) is one of the leading causes of visual impairment worldwide. In order to expand the myopia gene spectrum in the Chinese population, we investigated genetic mutations in a cohort of 27 families with HM from Northwest China by using whole-exome sequencing (WES). Genetic variations were filtered using bioinformatics tools and cosegregation analysis. A total of 201 candidate mutations were detected, and 139 were cosegregated with the disease in the families. Multistep analysis revealed four missen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The identification of pathogenic mutations in these genes promises to significantly enrich our understanding of the pathogenesis of HM. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of pathogenic mutations in these genes promises to significantly enrich our understanding of the pathogenesis of HM. 19 …”
Section: Discussionmentioning
confidence: 99%
“… 18 Another study recruited 27 eoHM families from the Ningxia Hui Autonomous Region, uncovering mutations in four genes ( CSMD1 , PARP8 , ADAMTSL1 and FNDC3B ). 19 Wang et al investigated 14 eoHM genes in a sizeable cohort and revealed ARR3 as the most common cause of Mendelian eoHM. 20 However, current genetic research on myopia across various provinces in China is insufficient, particularly in Shaanxi province, which is known for its high incidence of the condition (54.9% prevalence of myopia).…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence supported that high myopia facilitates the formation of cataracts [ 12 ]. Myopia is also coregulated by genetic and environmental factors [ 13 ]. Thus, genetic factors are indicated to contribute to the pathogenesis of high myopia-induced cataracts (HMC).…”
Section: Introductionmentioning
confidence: 99%
“… 58 For instance, a WES study involving 27 families has uncovered 201 candidate variants associated with HM. 59 Additionally, our previous study has shown that population-based WES can discover functional risk alleles and provide important clues to elucidate the cause of HM. 60 Therefore, large-scale genetic screening for school-aged children with HM could provide further insight into the intersecting contributions of biology and the environment.…”
Section: Introductionmentioning
confidence: 99%